Answer:f(g(0))= 1/5
g(f(0))= 7
Step-by-step explanation:
for f(g(0))=you solve for g(x) but you plug in 0 for x so g(0)= 8(0)+3
=3
so now you plug in the answer of the function of g(x) witch is 3 and plug it in as the x for F(x) so f(3)= 1/(3)+2
= 1/5
so f(g(0)) is equal to 1/5
Now for G(f(0)) you solve for f(x) by pluging 0 for x so F(0)= 1/(0)+2
=1/2
now you plug in 1/2 for the x of g(x) so g(1/2)= 8(1/2)+3
= 4+3
=7
so g(f(0)) is equal to 7
Hope this helps:)
Answer:
Plot
and ![-3](https://tex.z-dn.net/?f=-3)
Step-by-step explanation:
Given:
![|2n| = 6](https://tex.z-dn.net/?f=%7C2n%7C%20%3D%206)
Solving for the positive part of the equation:
![2n = 6 \\ \frac{2n}{2} = \frac{6}{2} \\ n = 3](https://tex.z-dn.net/?f=2n%20%3D%206%20%5C%5C%20%5Cfrac%7B2n%7D%7B2%7D%20%3D%20%5Cfrac%7B6%7D%7B2%7D%20%5C%5C%20n%20%3D%203)
Solving for the negative part of the equation:
![-2n = 6 \\ \frac{-2n}{-2n} = \frac{6}{-2} \\ n = -3](https://tex.z-dn.net/?f=-2n%20%3D%206%20%5C%5C%20%5Cfrac%7B-2n%7D%7B-2n%7D%20%3D%20%5Cfrac%7B6%7D%7B-2%7D%20%5C%5C%20n%20%3D%20-3)